The Problem Based Learning in Enhancing Students’ Critical Thinking for Reading Skills in English Teaching at Vocational School - Nurul Iskandar; Mustaji; Miftakhul Jannah; Soetam Rizky Wicaksono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The purpose of this research explained how Problem Based Learning (PBL) designed in teaching and learning English for Vocational School students in Indonesia. A PBL was used for overcoming critical thinking skill in teaching English at vocational school. The sample consisted of tenth grade of vocational school students who were recruited purposively. The research methodology used qualitative and qualitative method. Interview was used to get data about instructional and students’ needs. Questionnaire was used to obtain expert validation during teaching and learning process, and a test was used to obtain the effectiveness. The results of expert validation showed that the design of this learning strategy was good and can be used in learning English. It was effective in English as Foreign Language teaching strategy for vocational school in Blega of Bangkalan. Thus, it could be implemented in the teaching and learning English for vocational school students in enhancing students’ critical thinking.